CSR and financial performance: Linked by innovative activities - Majda Bastič; Matjaž Mulej; Mira Zore (Naše gospodarstvo / Our Economy, 2020)
The purpose of the present study was to investigate the relationships between different dimensions of corporate social responsibility (CSR), as well as the mediating role of innovation between CSR dimensions and financial performance. Data was collected with questionnaires from 321 managers of Slovene companies to test a conceptual model with structural equation modeling (SEM). The field-research results were that CSR is the most relevant dimension for employees. It positively influences CSR to the natural environment, to customers, and to the local community. The mediating role of innovation between CSR and financial performance was confirmed. The results also showed that CSR to the natural environment and CSR to customers positively affect innovation, while CSR to the local community had a negative impact. In addition, the positive impact of innovation initiated by CSR on financial performance was confirmed. The principal limitation of this study was its focus on Slovenian firms and the fact that data was obtained from only one manager in each firm. Slovene companies should consider the global initiatives supportive of CSR as the way to create opportunities for innovation and differentiation from other companies and increase their financial performance. The conceptual model developed and tested on the data obtained by Slovene managers gives new perspective on the impacts of social responsibility, innovation and financial performance. It highlights the areas in which the theory of social responsibility needs more research.
Keywords: M14; O3; M20; 330; corporate social responsibility (CSR); Slovene companies; innovation; financial performance; structural equation modeling (SEM)